Design and Control of a Library Service Robot - Đặng Xuân Ba; Huỳnh Trung Hiếu; Vũ Trọng Luật (Journal of Technical Education Science, 2024)
Nowadays, the use of robots as substitutes for humans has been increasingly prevalent. Robots are progressively integrating advanced technologies such as artificial intelligence, Internet of Things (IoT), and more, enabling them to operate autonomously like humans. Service robots are applied in many fields and industries such as health, education, rescuing, military, etc. This article presents design and control of an intelligent robot for library services, in which most advanced technologies are combined in a very reasonable way to create better experiences for readers and meet needs of a modern library. The robot is equipped with facial recognition capabilities, allowing it to identify and interact with individual users. Additionally, users can utilize the robot for tasks such as borrowing and returning books and searching for book information without visiting to service desks. Furthermore, the robot can detect and navigate around objects, furniture, and people moving within the library, ensuring safety for both users and the surrounding environment. Library managers can monitor and control the robot through an online interface, facilitating effective management and supervision of the robot’s activities. Experimental results have demonstrated effectiveness and feasibility of the developed robot in real-world operational environments.